2019
DOI: 10.1186/s43044-019-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Strain imaging to assess early effects of successful percutaneous balloon mitral valvotomy on left atrium mechanics

Abstract: BackgroundGlobal left atrial strain (LA) has been used as a novel assessment tool to evaluate left atrial function. However, not much has been investigated to study the effect of percutaneous balloon mitral valvotomy (BMV) in patients with rheumatic severe mitral stenosis on global LA strain. We studied the relationship between global left atrial (LA) strain and severe mitral stenosis and the effect of BMV on LA strain.ResultsA total of 29 patients satisfying the criteria for severe mitral stenosis underwent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…PTMC is generally associated with good outcomes with low procedural and long-term mortality, but with signi cant need for re-intervention in the future. [17][18][19] In term of left ventricular function, there is a notion that MS protects the LV, thus systolic function should be preserved [13]. Many studies have shown that the EF is indeed preserved pre and immediately post PTMC [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTMC is generally associated with good outcomes with low procedural and long-term mortality, but with signi cant need for re-intervention in the future. [17][18][19] In term of left ventricular function, there is a notion that MS protects the LV, thus systolic function should be preserved [13]. Many studies have shown that the EF is indeed preserved pre and immediately post PTMC [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Speckle tracking strain allows us to look at subclinical left ventricle (LV) and right ventricle (RV) dysfunction by analyzing Global Longitudinal Strain (GLS), Right Ventricle Free Wall Strain (RVFW-S) and left atrial dysfunction by looking at Left Atrial Reservoir Strain (LAr-S) [5][6][7][8]. With regards to subclinical LV and RV dysfunction, there are prior studies showing reduction in Global Longitudinal Strain (GLS) and Right Ventricle Free Wall Strain (RVFW-S), but the study population is small, and these studies only analyzed pre and immediate post PTMC values [7][8][9][10][11][12][13][14]. To our knowledge, this is the rst study that tracks all aspects of strain (GLS, RVFW-S and LAr-S) pre, immediately and 6 months post procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore patients with severe MS should be subjected to early and timely BMV so as to improve their LA function. 11,22 We also believe that intervention may have an impact on preventing these patients to develop atrial fibrillation (AF), RV dysfunction and improving their prognosis. In the study by Ancona et al 23 the degree of reduced LA systolic strain in patients with rheumatic MS correlated not only with worse cardiovascular outcomes during 3-year follow-up but also was the most powerful predictor of new onset AF at 4-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For all subjects, standard two-dimensional (2D), M-mode and Doppler echocardiograms were obtained according to the American Society of Echocardiography guidelines. 11 Baseline measurements included were LA dimension, LV internal dimension in diastole (LVID d ) and in systole (LVID s ) and LV ejection fraction (LVEF). MVA [?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation